Hubungan Pengetahuan dan Sikap Ibu tentang 1000 Hari Pertama Kehidupan (HPK) dengan Kejadian Stunting Pada Balita di Wilayah Puskesmas Gilingan - Khoirunnisa, Ariani; Kisnawaty, Sudrajah Warajati; Firmansyah, Firmansyah (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The prevalence of stunting in Surakarta City in 2023 has not yet reached the target, and the percentage of stunted children in the working area of Puskesmas Gilingan is above the city's average percentage. The issue of stunting can be attributed to inadequate maternal nutritional behavior during the First 1,000 Days of Life (1000 HPK), which may be influenced by mothers' lack of knowledge and poor attitudes. This study aims to examine the relationship between maternal knowledge and attitudes regarding 1000 HPK and the incidence of stunting in children within the working area of Puskesmas Gilingan.This research is classified as a descriptive quantitative study using a cross-sectional method conducted in the service area of Puskesmas Gilingan, involving 83 respondents. A questionnaire was used as an instrument to collect data on mothers' level of knowledge and attitudes, while children's nutritional status was determined by calculating the z-score based on height-for-age measurements. Data analysis was performed using the Spearman rank statistical test. The study findings indicate a significant relationship between maternal knowledge and attitudes regarding 1000 HPK and the incidence of stunting in children, as evidenced by a p-value of 0.000 (p < 0.05). Therefore, it can be concluded that maternal knowledge and attitudes concerning 1000 HPK are associated with the occurrence of stunting in children within the service area of Puskesmas Gilingan.